(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2023)
The interest in this work is understanding the conditions which contribute to the cyclic loading experienced by a tidal turbine. Tidal turbines are placed in locations with high flow speeds in order to extract maximum kinetic energy. These flow speeds combined with other environmental factors can lead to a complex operating conditions. When assessing turbine loading across a site, most models use ambient flow conditions, with very few codes including the impact of waves with currents. Previous studies have analysed the influence of wave conditions from measurements on the loading, through a consideration of the turbine not operating. Although tidal conditions are bi-directional, wave conditions do vary with direction and this combination will be investigated in this study. Full-scale site data was gathered at Le Raz Blanchard, a potential tidal site as part of the Interreg funded TIGER project. The focus in this study is on data gathered which provides both wave and current conditions over a period of 45 days. Loading on the turbine components is assessed through an efficient blade element momentum theory method, which is combined with a synthetic turbulence model to provide a time-varying onset flow. This work determines the impact of the measured waves, and the way in which they are analysed on the turbulence characteristics in the onset flow, specifically the interaction of waves with current and influence on the loading experienced on the turbine.